Partial Mole Coexistence with a Normal Live Fetus in Twin Pregnancy - Alkateeb, Saabh I.; Alkhalidy, Hala M. (Journal of the Faculty of Medicine Baghdad, 2019)
We present a case of dizygotic diamiontic twin pregnancy in which one fetus was normal with normal placenta, the 2nd fetus was normal appearing with partial molar placenta. All required investigation and clinical assessments were carried out and revealing partial molar pregnancy in one fetus and normal placenta of the other one. Maternal BhCG was high for  gestational age.The patient was a 31-year-old presented to Central Private Hospital; her gestational age was 22 weeks +5 days following IVF (after 10 years of primary infertility) of diazygotic diamiontic twin pregnancy as a case of vaginal bleeding from 8 weeks of gestation with uterine contractions.The patient had gestational DM & hyperthyroidism. Appropriate treatment regarding her conditions was implementedAll appropriate management was implemented. The patient continued to bleed. Within few days of admission she had premature uncomplicated labor with normal vaginal delivery (gestational age was23 Wks +3 days), both babies appeared normal, one placenta morphologically &histologically typical of H.mole. The other one completely was normal.Monitoring of serum BhCG and follow up transvaginal US was done until BhCG level returned to normal after 3 months of delivery without chemotherapy.Close monitoring of pregnancy from early stages and discussing the possible complications to mother and baby (such as baby may be chromosomally abnormal &may not survive) with parents is important to manage such complications.It is also necessary to have post-natal close follow up for maternal BhCG levels to assess any possibility of invasive mole or choriocarcinoma.